Corticosterone-induced postpartum depression induces depression-like behavior and impairs hippocampal neurogenesis in adolescent offspring via HPA axis and BDNF-mTOR pathway - Hongxiao Xie; Yanning Jiang; Xiumeng Zhang; Xinran Min; Jiuseng Zeng; Li Chen; Nan Zeng; Rong Liu (Neurobiology of Stress)
Postpartum depression (PPD) adversely affects the growth and development of the offspring, increasing the risk of various internalizing behaviorsduring adolescence. Studies have shown that corticosterone (CORT)-induced PPD affects neurogenesis in the offspring, which is closely related to the onset of depression. However, the underlying mechanisms of these changes in the offspring of PPD mothers remain unexplored. In this study, we demonstrated postpartum mice treated with high CORT experienced activation of the hypothalamic-pituitary-adrenal (HPA) axis, which induced depressive-like behavior and impaired maternal caring behavior. Furthermore, adolescent offspring of PPD mice exhibited depression-like behavior, and learning and memory deficits. These offspring also showed diminished levels of DCX+, decreased levels of synaptic proteins, and reduced dendritic spine density and length in hippocampus. Additionally, we detected increased serum stressed hormones and decreased hippocampal glucocorticoid receptor (GR) protein level in the offspring. We also found the offspring exhibited reduced expression of brain-derived neurotrophic factor (BDNF) and the phosphorylation tyrosine kinase receptor B (TrkB), protein kinase B (AKT), and mammalian target of rapamycin (mTOR) proteins in hippocampus. These results indicated that the behavioral deficits and neuronal damage observed in the offspring of PPD mice may be related to HPA axis dysfunction and inhibition of the BDNF-mTOR pathway. In conclusion, our findings confirm that CORT induces depression-like behavior and impairs maternal caring behavior in maternal mice, which in turn affects their offspring's emotion and cognitive behavior. This impact is characterized by the activation of the HPA axis and inhibition of the BDNF-mTOR pathway.